Selection of Trichoderma isolates for biological control of Sclerotinia minor and S. sclerotiorum in lettuce - Elias,Luciana Mecatti (2016)
ABSTRACT Lettuce drop is one of the most important and difficult-to-control diseases affecting lettuce in Brazil and worldwide. This study was carried out to select Trichoderma isolates antagonistic to Sclerotinia minor and S. sclerotiorum, aiming to develop biological control for this pathosystem in Brazil. Thirty-one Trichoderma isolates were obtained with the use of baits and were tested under laboratory conditions for their ability to control S. minor and S. sclerotiorum in seedlings of lettuce cultivar Tainá cultured in Petri dishes containing water-agar medium. Subsequently, four isolates effective for control and showing high sporulation under laboratory conditions were evaluated in greenhouse in two experiments carried out with both pathogens in lettuce seedlings of the same cultivar. Twenty-two isolates showed ability to control S. minor and S. sclerotiorum in the in vitro experiments. The isolates tested under greenhouse conditions, identified as T. asperellum (IBLF 897, IBLF 904 and IBLF 914) and T. asperelloides (IBLF 908), reduced lettuce drop of seedlings caused by both pathogens but were more effective against S. minor. Biological control is a promising technology for the management of lettuce drop, especially because S. minor is the predominant species in infested lettuce fields in Brazil.